Development of a Smart IoT-Integrated Watering System for Moth Orchid (Phalaenopsis amabilis) Cultivation in the SMASHTHETIC Greenhouse - Permanasari, Ayu Ratna; Harita Nurwahyu Chamidy; Bevi Lidya; Ari Marlina; Endang Widiastuti; In Jumanda Kasdadi (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
A greenhouse is a controlled environment designed to enhance plant productivity by regulating microclimatic conditions. However, in many greenhouse systems, the irrigation process is still performed manually, resulting in suboptimal water use efficiency and inconsistent watering schedules. The SMASHTHETIC greenhouse serves as a cultivation facility for the moth orchid (Phalaenopsis amabilis), which requires precise control of substrate moisture and ambient humidity to ensure optimal growth and flowering. This study aims to design and implement an automatic irrigation system based on Arduino and the Internet of Things (IoT) to improve irrigation efficiency in the SMASHTHETIC greenhouse. The system consists of a soil moisture sensor, Arduino microcontroller, Wi-Fi module (ESP8266/ESP32), and actuators such as a water pump and solenoid valve to regulate water flow. IoT integration enables real-time monitoring and remote control via web and smartphone applications. Experimental results show that the system automatically adjusts watering frequency and duration based on soil moisture data, providing convenience for users and reducing manual intervention. Therefore, this study demonstrates that the integration of Arduino and IoT technologies in greenhouse irrigation supports the development of smart agriculture practices that are more efficient, sustainable, and productive.